2010
DOI: 10.1016/s2255-4971(15)30384-0
|View full text |Cite
|
Sign up to set email alerts
|

Hemiarthroplasty in the Treatment Fractures of the Femoral Neck

Abstract: Objective: To epidemiologically and clinically evaluate patients with displaced femoral neck fractures that were surgically treatment with cemented hip hemiarthroplasty. Methods: All patients with displaced femoral neck fractures (Garden III and IV) who underwent cemented hip hemiarthroplasty using a unipolar prosthesis (Thompson), by means of a posterolateral access between June 2005 and September 2008 were retrospectively evaluated. Results: Seventy patients were initially evaluated. Their mean age was 83.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…These data are in agreement with several other studies in which there was predominance of female patients ranging from two to eight women per man. 1 , 10 , 12 , 20 These proportions of 1.4:1 were also found in a study carried out by Rocha et al 21 The difference found between the sexes is partly explained by the lower bone mineral density among females after the menopause. 22 …”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…These data are in agreement with several other studies in which there was predominance of female patients ranging from two to eight women per man. 1 , 10 , 12 , 20 These proportions of 1.4:1 were also found in a study carried out by Rocha et al 21 The difference found between the sexes is partly explained by the lower bone mineral density among females after the menopause. 22 …”
Section: Discussionsupporting
confidence: 66%
“…In a study conducted in the city of São Paulo, Ono et al 10 observed that the mean age of patients with fractures of the femoral neck who underwent partial hip arthroplasty was 83.1 years (range: 58–99). Like in the present study, Chikude et al 12 reported a mean age of 83 years in an analysis on patients with fractures of the femoral neck.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, one study had a longer follow-up period, with mortality at 24 and 48 months of 26% and 40% in patients without delirium and of 36% and 60% in patients with delirium during hospitalization after a fracture [31]. the predictors identified in this systematic review were grouped into 1) demographic factors: older age [14,17,[20][21][22][23]33,34] and male sex [14,17,33]; 2) clinical factors: comorbidities [15,16,18,20,23,31], high scoring in surgical risk assessment scores [13,17,21,24,33,34,38], functional status before fracture [17,31,33,36], and cognitive/neurological disorders [15,23,31,39]; and 3) intra-hospital factors: infections [15,21,23,26,30] and the time between hospitalization and surgery [20,21,34,35]. Only one study addressed prolonged hospitalization as a factor associated with mortality [16] (S1Table).…”
Section: Resultsmentioning
confidence: 99%